Covid-19’s Effect on Lecturer Performance and Management Functions in Educational Implementation - Yusaini, Yusaini; Muslim, Buhori; Rusli, Rusli; Darmawati, Darmawati; Hasyim, Syarifuddin (SCAD Independent, 2024)
Virus Covid-19 spread very quickly. One of the sectors affected by this pandemic is education. It’s felt at the State Islamic Higher Education Institutions (PTKIN) in Aceh. Covid-19 has influenced the function of college management and the performance in fostering education and teaching. This article was intended to explain research findings on the impact of COVID-19 and management functions on the performance of lecturers in conducting education and teaching at the PTKIN Aceh. This research was carried out ex post facto on a causal basis to identify the causal relationship between the variables studied, namely the Covid-19 pandemic, management function, and lecturer performance. Research showed that COVID-19 affected the management function of the campus but did not affect the performance of the lecturers in performing education and teaching at the PTKIN Aceh. COVID-19 could have a significant positive impact on the performance of education and teaching tasks at Aceh PTKIN because it forced the lecturers to deliver new techniques in teaching performance, which is a Virtual Learning application.